2014
DOI: 10.1152/jn.00493.2013
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning of novel dynamics is not represented in a single global coordinate system: evaluation of mixed coordinate representations and local learning

Abstract: Successful motor performance requires the ability to adapt motor commands to task dynamics. A central question in movement neuroscience is how these dynamics are represented. Although it is widely assumed that dynamics (e.g., force fields) are represented in intrinsic, joint-based coordinates (Shadmehr R, Mussa-Ivaldi FA. J Neurosci 14: 3208–3224, 1994), recent evidence has questioned this proposal. Here we reexamine the representation of dynamics in two experiments. By testing generalization following changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 54 publications
10
84
1
Order By: Relevance
“…The multitude of processing strategies accounted for by C-SMB is consistent with the many indications that movement representations may be coded in very different ways, such as verbal, egocentric spatial, allocentric spatial, goal postures of effectors, and joint angles (Andresen & Marsolek, 2012;Bapi, Doya, & Harner, 2000;Berniker, Franklin, Flanagan, Wolpert, & Kording, 2013;De Kleine & Verwey, 2009;Hikosaka et al, 1999;Panzer, Gruetzmacher, Fries, Krueger, & Shea, 2011;Shea et al, 2011;Verwey & Abrahamse, 2012;Verwey et al, 2010). Indeed, recent sequencing studies with the flexionextension task (Kovacs, Muhlbauer, & Shea, 2009;Panzer et al, 2011), the serial RT task (Goschke & Bolte, 2012;Tubau et al, 2007), and with the discrete sequence production task (Verwey & Abrahamse, 2012;Verwey & Wright, 2014), all indicate that with practice several of these movement sequence representations develop concurrently (Berniker et al, 2013).…”
Section: Coding Movement Sequencessupporting
confidence: 72%
See 1 more Smart Citation
“…The multitude of processing strategies accounted for by C-SMB is consistent with the many indications that movement representations may be coded in very different ways, such as verbal, egocentric spatial, allocentric spatial, goal postures of effectors, and joint angles (Andresen & Marsolek, 2012;Bapi, Doya, & Harner, 2000;Berniker, Franklin, Flanagan, Wolpert, & Kording, 2013;De Kleine & Verwey, 2009;Hikosaka et al, 1999;Panzer, Gruetzmacher, Fries, Krueger, & Shea, 2011;Shea et al, 2011;Verwey & Abrahamse, 2012;Verwey et al, 2010). Indeed, recent sequencing studies with the flexionextension task (Kovacs, Muhlbauer, & Shea, 2009;Panzer et al, 2011), the serial RT task (Goschke & Bolte, 2012;Tubau et al, 2007), and with the discrete sequence production task (Verwey & Abrahamse, 2012;Verwey & Wright, 2014), all indicate that with practice several of these movement sequence representations develop concurrently (Berniker et al, 2013).…”
Section: Coding Movement Sequencessupporting
confidence: 72%
“…Indeed, recent sequencing studies with the flexionextension task (Kovacs, Muhlbauer, & Shea, 2009;Panzer et al, 2011), the serial RT task (Goschke & Bolte, 2012;Tubau et al, 2007), and with the discrete sequence production task (Verwey & Abrahamse, 2012;Verwey & Wright, 2014), all indicate that with practice several of these movement sequence representations develop concurrently (Berniker et al, 2013).…”
Section: Coding Movement Sequencesmentioning
confidence: 99%
“…With regard to novel force field learning, there is considerable evidence that sensorimotor adaptation is a form of local learning that does not generalize to very different circumstances (Berniker et al 2013(Berniker et al , 2014Donchin et al 2003;Gandolfo et al 1996;Krakauer et al 2000;Lackner and Dizio 1994;Ostry 2007, 2010;Thoroughman and Shadmehr 2000). These studies are in line with our finding that movement path errors during generalization were the same for the narrow and broad groups.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent force field adaptation study by Berniker et al (2014), patterns of generalisation could not be explained by representation in any single coordinate system when intralimb reaching was tested with different shoulder, elbow and wrist angles.…”
Section: Post Training Twitches In the Testing Posturementioning
confidence: 84%
“…However, more recent error-based learning studies, i.e. adaptation to force field or visuomotor perturbation, have suggested that motor learning could be represented in a combination of extrinsic and intrinsic coordinate frames (Berniker et al, 2014;Brayanov et al, 2012;Carroll, et al, 2014).…”
Section: Post Training Twitches In the Testing Posturementioning
confidence: 99%